Behind the economic figures : large-scale mining and rural poverty reduction in Zambia : the case of Kansanshi Copper Mine in Solwezi : a thesis presented in partial fulfillment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, Palmerston North - Cheelo, Kingsley Haanyembe (Massey University, 2008)
Mining is promoted as a lead-economic sector in most mineral-rich countries. Depending on the contemporary global development ideology, the place of mining within the development industry has always been justified. Under the poverty reduction agenda, which took the centre-stage in the late 1990s and early 2000s, it has been argued in theory that investments, especially in large-scale mining would lead to poverty reduction in mining communities through opening up economic opportunities in which they can participate; increase their capabilities to participate in the local economies; enhance their security by reducing their vulnerability and exposure to risks; and empowering them to participate in issues that affect their lives. Zambia as a mineral-rich country adapted the linkages between mining and poverty reduction and promoted the development of Kansanshi copper mine within the country's macroeconomic policy framework of achieving sustained economic growth and poverty reduction. Because of the positive response of the mining sector to huge investments, the domestic economy has been recording positive growth rates in excess of 5 percent since the beginning of the 2000s, with other economic indicators such as inflation, currency appreciation, and balance of payments recording positive trends. Applying the Sustainable Livelihoods Framework (SLF), this thesis explores the extent to which the development of Kansanshi copper mine in Solwezi has impacted on local people's livelihoods in the context of the four linkages between mining and poverty reduction promulgated in theory. It comes out clearly in the thesis that the development of the mine has opened up economic opportunities that are in areas that do not allow the full participation of local people; the development of local people's capabilities is either minimal or non-existent; mine development enhanced local people's vulnerability and exposure to risks through displacement and seizure of productive systems; and disempowered them through the way mining and land rights were obtained from the government. The thesis concludes on the note that since mining development cannot be stopped, there is need for governments to deliberately cater for local people who often struggle to fit within the transformed local economies through comprehensive implementation frameworks that promote interaction among parties involved and improved communication channels, skills training and provision of relevant resources such as agricultural inputs and microcredit facilities.
Keywords: Poverty -- Zambia; Rural poor -- Zambia; Rural development -- Zambia; Zambia -- Rural conditions; Zambia -- Economic policy; Copper mines and mining -- Social aspects; Zambia -- North-Western Province -- Solwezi; Copper mines and mining -- Economic aspects